(untitled) (Nuntius Antiquus, 2008)
This Portuguese Antigone, inspired by the Sophoclean play, puts the accent on different topics. Following Antigone’s behaviour from her childhood, it creates a group of female characters around the heroine and aims at her development as someone growing up from a disturbed family. Her irreverency is not put in service of any ideal, it is the consequence of her desadaptation.